Frequency of genomic mutations mediating resistance of Mycobacterium tuberculosis isolates to rifampicin in Northern Morocco - Karimi, Hind; Oudghiri, Amal; En-nanei, Latifa; Mzibri, Mohammed El; Laglaoui, Amin; Chaoui, Imane; Abid, Mohammed (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
Drug resistant tuberculosis (DR-TB) is challenging particularly in developing countries. As such, a previous investigation gave the first insight into the mutational status of the Rifampicin Resistance Determining Region (RRDR) of rpoB gene among a restricted number of MTB patients’ residents in the Northern Morocco. The purpose of this study was to investigate rpoB mutation types and frequencies associated with resistance to Rifampicin in a larger panel of MTB patients and to evaluate the usefulness of these mutations to improve the diagnosis of resistance to Rifampicin. A panel of 301 consecutive sputum samples belonging to patients suscpected of having TB from Northern Morocco was collected at the Pasteur Institute of Tangier between 2014-2017. Samples were subjected to conventionel microbiological tests. Evaluation of rpoB muational status was assessed by PCR amplification and sequencing of the RRDR of the rpoB gene. DST results showed that 26.4% of strains were MDR. Sequencing results reported single point mutations in 36 of 65 RIFR isolates of which two had two mutations. Aminoacid substitutions in the codon Ser531Leu occurred at the highest frequency (34.46%). Overall, 10 aminoacid substitutions have been registered, and the H526S substitution was reported for the first time. The present study highlighted that resistance to RIF is a reliable marker of MDR-TB, the common mutations successfully detected in the rpoB 531, rpoB526 and rpoB516 codons provide a foundation for the implementation of molecular approaches such as Hain and GeneXpert as a routine tests to detect DR-TB. However, considerable work is still necessary to identify extensive mutations associated with DR-TB.